167 INTERMITTENT ANDROGEN SUPPRESSION IN THE TREATMENT OF PROSTATE CANCER: AN UPDATE OF THE VANCOUVER EXPERIENCE. Issue 1 (1st January 2007) - Zappavigna, C.; Studd, R. C.; Hurtado-Coll, A.; Goldenberg, S. L.
Abstract : Objective: Intermittent androgen suppression (IAS) is a feasible treatment for advanced prostate cancer (CaP). We review the long-term follow-up of an IAS cohort. Methods: 106 men with a median age of 65.7 years (48.8-86.9) were identified who had been commenced on IAS. At IAS commencement, 16 patients had metastatic disease (MD, lymph node positive or positive bone scan) and 90 had localized disease (LD). Luteinizing hormone-releasing hormone agonist monotherapy was given every 1 to 4 months. A treatment cycle is defined as the time between the initiation of medical castration to the time point of the start of the next treatment phase. Treatment was resumed when the serum PSA increased to an arbitrarily chosen value. Cycles were continued until tumor progression to androgen independence (AI) or treatment was changed to continuous androgen suppression due to patient choice. Results: The median follow-up for patients presenting with MD and LD was 47 (12-129) and 43 months (9-126), respectively. The median cycle length and median time off therapy were 20 and 12 months and 25 and 16 months for MD and LD, respectively. The median pretreatment PSA and Gleason score (GS) for LD were 10.2 ng/mL (0.2-450) and 7 (3-9). For MD, the presenting PSA (> 20 vs < 20), and GS (< 7 vs ≥ 7) were not predictive for total time spent off therapy. For LD, the presenting PSA was predictive of cycle length and time off therapy (PSA > 20; 20.7 and 12.2 months vs PSA < 20; 33.2 and 24.6 months, p = .007). The GS was not predictive. Twenty-one patients have progressed to AI. The median time to AI for MD and LD was 58.6 (9.2-125.5) and 56.4 months (16-120), p > .05. Five patients with AI have died; the mean time to death from development of AI was 1.7 years. Conclusion: Longer-duration follow-up of a single cohort supports IAS as a viable treatment option for men with advanced CaP. The PSA at the start of IAS is predictive of cycle length and time spent off therapy for patients with nonmetastatic disease.